Peningkatan Kemampuan Mengenal Warna Pada Anak Usia Dini Dengan Media Menara Hanoi Di Raudhatul Athfal Al-Hikmatul Mubarokah - Jubaedah, Endah; Siti latifah, Azkiya (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2022)
This research was motivated by observational data showing the acquisition of the results of the ability of early childhood at RA Al-Hikmatul Mubrokah in the ability to recognize colors by finding several problems including; children who do not know colors, children who cannot distinguish colors correctly and children who are still confused in the pronunciation of colors. The purpose of this study is the use of the Hanoi Tower media in improving the ability to recognize colors at RA Al-Hikmatul Mubarokah referring to three assessment indicators, namely recognizing, communicating and classifying colors by referring to the assessment criteria. The limitation of the problem in this study is about increasing the ability to recognize colors in early childhood at RA Al-Hikmatul Mubarokah. This research methodology uses classroom action research with a qualitative descriptive method. The research design uses a spiral model developed by Kemmis and Mc. Taggart. Broadly speaking, it consists of four stages, namely: planning, implementation, observation and reflection. In the flow of activities, the implementation and observation stages are carried out simultaneously. Based on the results of the study, the increase in the ability to recognize color in early childhood at RA Al-Hikmatul Mubarokah has increased, this can be seen from the accumulated data from the pre-cycle with a percentage of 52.5%, in the first cycle it increased by an increase of 15% with a percentage of 67.5% and in the second cycle it increased again with an increase of 17% with a percentage of 85%. Keywords: Upgrade; Hanoi tower; Recognize Colors